G246(P) Closing the ductus arteriosus in preterm infants. a review of present treatment strategies and developing a disease staging protocol. (12th March 2018) - Raychaudhuri, H; Bahadur, A; Alam, M; Nayak, S; Ali, I
Abstract : Background: The ductus arteriosus (DA) is an important structure in foetal life. Closure of the DA is an essential part of postnatal adaptation. Closure of the DA is initiated by an increase in oxygen and changes in pulmonary and systemic blood pressure. In preterm infants, failure of DA closure after birth can be associated with an increased incidence of chronic lung disease (CLD), intraventricular haemorrhage (IVH) and necrotizing enterocolitis (NEC). Prostaglandin inhibition using indomethacin or ibuprofen is the standard strategy to close the DA. Surgical closure and interventional device closure of the DA are an alternative option. Appropriate timing for closing the duct still remains a debatable topic. Various staging methods have been proposed based on Echocardiographic and clinical parameters to help clinicians make a decision. This study aims at assessing the effect of closing a DA on the overall morbidity and mortality in preterm infants and further interrogating available evidence on the best practice and optimum time for closing the DA. We designed a PDA staging protocol based on available evidence which will help clinicians decide on closing the DA. Methods: We conducted a review of literature and results from 10 different papers were assessed and analysed for this study. Conclusion: Closure of the DA in the first few weeks of life may provide short-term benefits. The long-term effects of untreated PDA in extremely premature infants remain unclear. Significant changes in management have evolved in the recent years including early surgical ligation and transcutaneous device closure but the evidence to support these changes are minimal. Carefully constructed clinical trials are required to compare the effects of present treatment strategies with more conservative approaches. Clinical and echocardiographic PDA scoring systems should be incorporated into the routine care of preterm infants and used to justify any treatment undertaken.